ANALISIS STRATEGI PEMASARAN MELALUI DIGITAL MARKETING PADA UMKM DESA TEGALREJO, KABUPATEN PROBOLINGGO - Taufikurrahman, Taufikurrahman; Dian Rahmatika, Ajeng; Maulana, M. Reza; Cendrawati, Vinda; Kusuma Wardani, Renata Dian; Ayu Rahmawati, Diya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research activity focuses on branding and Digital Marketing of MSMEs in Tegalrejo Village, Probolinggo. Tegalrejo Village, located in Probolinggo, is a village that has various types of MSMEs. This study uses a qualitative descriptive method, namely research that aims to provide an overview of the processes and results of MSMEs in Tegalrejo Village in product branding. Data collection techniques were obtained from direct observation and literature study. Digital Marketing for MSMEs serves as a communication link between sellers and consumers. Proper utilization can be used as a marketing medium for MSMEs. Digital Marketing provides more benefits for MSMEs because of the broad market reach they get. Apart from Digital Marketing, there is branding for MSMEs that needs attention. Branding can identify the goods or services of a business so as to differentiate it from its competitors. Logo design becomes a business identity. Logo visualization doesn't have to match the product. But still have to be able to describe the product. The logo design must also be suitable, that is, it can be applied to all needs. This study aims to determine the effect of digital marketing and product branding on MSMEs in Tegalrejo Village. The results of this study indicate that SMEs have made progress in marketing their products